Natural colorants from plant pigments and their encapsulation: An emerging window for the food industry. (January 2022) - Ghosh, Susmita; Sarkar, Tanmay; Das, Arpita; Chakraborty, Runu
Abstract: Color is considered to be the primary feature perceived by the senses that represent a crucial role for centuries in the acceptability of foods to enhance their actual appearance and quality. Plant pigments, the impeccable natural source of color, display enormous potential to substitute many of the synthetic colorants. Chlorophylls, carotenoids, anthocyanins, and betalains are the extensive classes of natural colors contributing comprehensive color shades to foods. There are good perspectives for the inclusion of plant pigments in the food industry. Their incorporation into food products is very challenging, as they are chemically unstable and exhibit poor bioavailability. Encapsulation is an excellent process to enhance its bioaccessibility, digestibility, and controlled release. During food fortification, efficient encapsulation technologies are needed to prevent the degradation of pigments and reserve their bioavailability in the human gastrointestinal system. The development of cost-effective and viable technologies for the preparation of natural food color and its application in foods is a great challenge and a major need of the day. Highlights: Color is associated with flavor, safety, and nutritional value of foods. Encapsulation protects pigments against deterioration and to improve their effectiveness in the food industry. Micro and nanoencapsulation are revolutionary approaches for controlled and targeted release of pigments. Encapsulated pigments can be utilized to produce functional food products.